Heterogeneity Among Strains of Mycoplasma granularum and Identification of Mycoplasma hyosynoviae, sp. n - Ross, R. F. (1970)
Twelve filtrable, pleomorphic organisms isolated from swine joints and respiratory tracts had typical colonial and microscopic characteristics of mycoplasmas. They resisted penicillin and did not revert to cell wall-producing bacterial forms in media devoid of bacterial inhibitors. The morphological and growth characteristics of these mycoplasmas were similar to those described previously for Mycoplasma granularum. However, a new name, M. hyosynoviae, is proposed for them since they differed biologically, serologically, and electrophoretically from the prototype strain of M. granularum. M. hyosynoviae required sterols, was stimulated by gastric mucin, and metabolized arginine; however, it did not metabolize urea, ferment glucose, or reduce tetrazolium. The organism produced “film and spots” on horse serum-supplemented medium and produced alpha hemolysis of guinea pig and sheep erythrocytes; however, it did not digest serum, produce phosphatase, or hemadsorb guinea pig or swine erythrocytes. M. hyosynoviae was distinguished from three other swine mycoplasmas, M. granularum, M. hyorhinis, and M. laidlawii, by means of acrylamide gel electrophoresis, growth inhibition, metabolic inhibition, and immunodiffusion techniques. It was also serologically and electrophoretically distinct from 13 additional non-swine mycoplasmas which require sterols and metabolize arginine.